Meningitis Vaccination Compliance Among Umrah Pilgrims In Indonesia: A Narrative Review - Alwan Zakki Nozomi; Irfansyah Baharuddin Pakki; Akhmad Azmiardi (Faculty of Public Health Mulawarman University, Indonesia, 2025)
Background : Umrah pilgrimage involves large gatherings of people from around the world, posing a high risk of disease transmission, especially meningococcal meningitis. Therefore, meningitis vaccination is mandatory as an absolute requirement for departure to prevent outbreaks. Although vaccination is mandatory, challenges related to the timeliness and compliance of vaccination at Port Health Offices (KKP) remain a crucial issue in Indonesia. This narrative review aims to synthesize and describe the meningitis vaccination compliance among Umrah pilgrims in Indonesia Objective : summarize, analyze, and interpret research results related to meningitis vaccination compliance among Umrah pilgrims Research Methods/ Implementation Methods : This review uses a narrative review method by analyzing 14 journal articles obtained from accredited journals from 2020 to 2025. The criteria for these articles are articles with independent variables focusing on factors related to vaccination compliance with vaccination compliance outcomes, articles with analytical observational designs. Selected articles were analyzed descriptively and narratively Results : results of the analysis show that the factors of knowledge and attitude of pilgrims are related to punctuality and vaccination compliance. In addition, support from the Umrah Travel Organizer (PPIU) or travel agent is also a predictor of compliance Conclusion/Lesson Learned : Compliance with meningitis vaccination among Umrah pilgrims is influenced by internal factors (knowledge and attitude) and external factors (travel support and PPIU support). The main recommendations are to strengthen education focused on the timing of vaccine administration and to improve effective coordination/socialization between KKP and PPIU to bridge the policy implementation gap